An activity theory approach to study barriers of faculty regarding technology integration in higher education - Castro, Willy (2016)
Information and communication technologies are instruments for supporting new ways of teaching and learning. Nevertheless, its impact concerning scope has not reached the expected level. This strain between benefits and impact has been inquired from the perspective of barriers of teachers to use technology. Ertmer’s approach establishes first-order and second-orders barriers as hinderers for teacher’s adoption of technology. The study intends to answer what are the barriers existing in the socalled enthusiastic faculty teachers regarding technology integration in Education? Findings call for a reconceptualization in the study of barriers arguing that the teaching process is a complex and dynamic activity that needs to be examined from a collective perspective. Cultural-Historical Activity Theory is the theoretical framework used in the study. It concludes with the necessity of overcoming the existing dichotomies between enthusiastic-resistant teachers, the intrinsic-extrinsic barriers, and claims for passing from an individual to a collective approach to ICT integration in education.